Task-Dependent Modulation of Effective Connectivity within the Default Mode Network - Li, Baojuan; Wang, Xiang; Yao, Shuqiao; Hu, Dewen; Friston, Karl (Frontiers in Psychology, 2012)
The default mode network (DMN) has recently attracted widespread interest. Previous studies have found that task related processing can induce deactivation and changes in the functional connectivity of this network. However, it remains unclear how tasks modulate the underlying effective connectivity within the DMN. Using recent advances in Dynamic Causal Modeling (DCM), we study the effective connectivity of resting state networks. The current fMRI study investigated the modulatory effect of (gender judgment) task performance on directed connectivity within the DMN. Sixteen healthy subjects were scanned twice: at rest and while performing a gender judgment task. Group independent component analysis was used to decompose the functional images into spatial independent components. Four subject-specific regions of interest (ROIs) were defined according to the ensuing default mode component: the posterior cingulate cortex, the left lateral parietal cortex, the right lateral parietal cortex and the medial prefrontal cortex. Effective connectivity among these regions was then characterized with stochastic DCM, revealing enhanced (extrinsic) between region connectivity within the DMN during task sessions – and a universal decrease in (intrinsic) self inhibition – relative to resting sessions. These results suggest a distributed but systematic modulatory effect of cognitive and attentional set on the effective connectivity subtending the DMN: an effect that increases its sensitivity to inputs and may optimize distributed processing during task performance.